Ai Weiwei - Smith, Karen, B.A.; Obrist, Hans-Ulrich.; Fibicher, Bernhard; Ai, Weiwei (London ; New York : Phaidon, 2009)
"The first comprehensive monograph on this key figure in China's burgeoning art scene. Often working with ancient materials - beams from destroyed temples, Han dynasty urns - Ai Weiwei (b.1957) creates ingenious sculptures that break new artistic ground while commenting on the rapid transformation of contemporary China. Ai Weiwei's work is consistently innovative and unmistakably original, ranging from his sculptures and photographs to his numerous architectural commissions, and recalls the work of his artistic forebears Marcel Duchamp, Joseph Beuys and Andy Warhol. A towering figure whose influence can be seen in the multiplicity of his roles: not just an artist, designer and architect, but also curator, publisher, web blogger and cultural compass for an entire generation of Beijing artists."--BOOK JACKET.
Interview - Hans Ulrich Obrist in conversation with Ai Weiwei. Survey - Karen Smith. Focus - Bernard Fibicher, Working Progress (Fountain of Light). Artist's Choice. Artist's Writings.
boek
Keywords: Ai, Weiwei